Incidence of congenital syphilis in children residente in the city of Guanambi – BA (Research, Society and Development, 2023)
Introduction: Congenital syphilis (CS) is a disease caused by the vertical transmission of the bacterium Treponema pallidum, through the contaminated pregnant woman to the fetus. Objectives: To verify the incidence of congenital syphilis in children living in the city of Guanambi-BA. Materials and methods: This is a descriptive study with a quantitative approach, whose data were obtained from the Department of Informatics of the Unified Health System (DATASUS), from the Notifiable Diseases Information System (SINAN), considering the notified cases of CS, during the years 2018 to 2021. Results and discussion: The sample consisted of 13 confirmed cases notified of CS in the city of Guanambi, with the highest number of cases between the years 2018 and 2020. age of children aged up to 6 days (92.31%), brown (46.15%) and female (46.15%). The study also identified the predominance of the maternal age group between 25 and 29 years (38.46%), where 92.31% of the women reported having performed prenatal care, 46.15% of the women reported having performed the treatment even during pregnancy, however, 61.54% of the partners stated that they had not undergone treatment. Final Considerations: The findings in this study showed a relevant number of confirmed cases that were reported of congenital syphilis in the city of Guanambi, in addition, it demonstrated, as an outcome, that adequate prenatal care and timely treatment of mothers and infected partners potentially reduces the occurrence of congenital syphilis.